Photodegradation of three stormwater biocides. Issue 1 (2nd January 2017) - Minelgaite, Greta; Nielsen, Asbjørn Haaning; Pedersen, Morten Lauge; Vollertsen, Jes
Abstract: Photodegradation of carbendazim, diuron and terbutryn was investigated at controlled laboratory conditions under UV light and under natural sunlight. Demineralized water and two different waters from stormwater retention ponds were used. An observed decline in biocide concentration was related to the accumulated light energy during the degradation time. Diuron and terbutryn were degradable under UV light following 1 st order degradation kinetics, while no significant decrease of carbendazim was observed throughout the duration of experiments. Photodegradation of diuron and terbutryn was slightly faster in demineralized water compared with pond water. The outdoors experiments showed limited degradation of the compounds for the duration of the test (8–17 days). The results emphasize the importance of water type, the wavelength and energy of the light when investigating pollutant's photo fate. Also, this study indicates that photodegradation is not a major process contributing to the removal of carbendazim, diuron and terbutryn in stormwater retention ponds.